(untitled) (Journal of Oriental Studies, 2018)
culture of the Turkish people. Records Orkhon-Yenisei, «Divany-latyshi-turki», Daniindend-Nam, «Book Korkyt-Ata», Solt-nam are considered as one of such works. Among these works the certain place is taken by the work of Yazyzhoglu Ali under the name «Seldzhuknameh» or also named as «TauarrihAli-seldzhuk», «Tarija Alya seldzhuk» or Oguz-nameh which is considered as the heritage of the Turkic world. This work has been written by Yazyzhogl Ali in 1436 in the period of the Second Murat’s governing. «Seldzhuknameh« is very rich with depth of sense and sharpness of a plot. The Mongolian and some Turkic tribes, such as Uyghurs, kipchak, kanglara, karluk, etc., are considered as the symbols of history of oguz. It is also told in detail about the origin of the name of the tribe of oguz, their symbolics and totems. Also Oguz symbolics are mentioned in this work which were written by gold ink. Yazyzhoglu, using various sources, has told in detail about such great people as Korkyt Ata, Tkhaki bin LukmanKhan – Seldzhuk’s father, the founder of the state of the Seljuks – Seldzhuk Beck (? – 1009), the Gaznavi’s governor Mahmoud Sultan (998-1030), Tugril Beck (1037-1063) Sultan Al-Arslan Sultan (1063-1072), Malika Shah (1072-1092), Berkayarukh (1094-1105), Mahomed Sultan (1105-1118), Mahmoud II (1118- 11314), Mesud Sultan (1134-1152), Giyadaddin Kakhir, the Alawite Keysukat, Othman Ghazi, etc, and also about the periods of their life. In addition to it, information on the Turks who have lodged in Anatoly and on the cities of Anatolii are also provided in this work. The historical work «Tavarikh al-Seldzhuk» is also investigated in this article (Seldzhuknam). The importance of Turkish language, history and culture is being proved as well.